ORGANOLEPTIC TESTS AND ANTIOXIDANT ACTIVITY OF BLACK SOYBEAN (GLYCINE SOJA L) SUPPLEMENTED TAMARILLO(SOLANUM BETACEUM CAV) - Irwanto, Reno; Novia, Reni; Rantika, Windy (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Degenerative disease refers to metabolic syndrome which occurs as a result of an unhealthy lifestyle. An unhealthy diet results in the emergence of large amounts of free radicals. High free radical content can disrupt cells and their genetic material which can result in degenerative diseases. Antioxidants are compounds that function to protect body cells from damage caused by free radicals that cause degenerative diseases. Soybean juice added with tamarillo is a food ingredient that is a source of antioxidants. The aim of the research was to obtain the best Dutch eggplant formula added to soy milk. The research method used was a Completely Randomized Design (CRD) which involved four additional treatments of Dutch eggplant, namely P1 (50 mL), P2 (55 mL), P3 (60 mL) and P4 (65 mL). Research activities were initially carried out by testing the organoleptic products using the hedonic method by 70 untrained panelists. Product testing is carried out using Then the best product testing results are continued to be tested for antioxidant content. Antioxidant testing The results of the organoleptic test research obtained the highest scores for the color attribute 5.69 (P3), aroma 5.23 (P2), taste 6.09 (P1), texture 4.76 (P1), and overall 5.81 (P1). Based on organoleptic tests, the best formula is 60 mL (P3) then the antioxidant activity test is 0.3374 ppm. The conclusion in this study shows that the best formula in terms of color, taste and overall black soybean juice added with Dutch eggplant has significant antioxidants.